Posterior sagittal anorectoplasty in anorectal anomalies: clinical, manometric and profilometric evaluation - Pedro Félix (2007)
CONTEXT AND OBJECTIVE: Anorectal malformations comprise a spectrum of anomalies that continue to be difficult to treat, even today. The aim was to evaluate the fecal continence of children who underwent posterior sagittal anorectoplasty due to anorectal malformations, via computerized anorectal manometry and profilometry. DESIGN AND SETTING: Prospective study at Universidade Federal de São Paulo. METHOD: 82 patients (56.1% boys; 43.9% girls) of mean age 85.5 months were evaluated. They were divided into continent, partially continent and incontinent groups. Age, sex, manometric variables and profilometric parameters were studied. The results were statistically analyzed. RESULTS: Among the 82 patients, 37.8% were continent, 25.6% were partially continent and 36.6% were incontinent. The overall mean resting pressure was 22 mmHg, and the means for the continent, partially continent and incontinent groups were, respectively, 30.7 mmHg, 23 mmHg and 14.7 mmHg. The overall mean pressure response to voluntary contraction was 56 mmHg, and the means for the groups were 65.4 mmHg, 55.8 mmHg and 46.6 mmHg, respectively. The rectosphincteric reflex was absent in 82.9% of the cases. In the profilometry analysis for all patients together, blue (20 to 50 mmHg) and yellow (50 to 80 mmHg) were predominant, and there was a similar distribution for the continent and partially continent patients. However, among the incontinent patients, green (< 20 mmHg) and blue prevailed. CONCLUSIONS: Manometric and computerized profilometric analyses were an excellent method for postoperative evaluations on patients with intermediate and high anorectal anomalies, and for therapeutic planning.